2011
DOI: 10.1007/s10151-011-0740-2
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer metastatic to the rectum: a case report

Abstract: Rectal metastasis from breast cancer is very rare. The presented case emphasizes the need to keep in mind this possibility and at all times associate the emergency condition with the related history of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Although histopathological observation is often used to distinguish ductal from lobular carcinomas, the first and second results were contradictory. The patient may encounter tubulolobular carcinoma, a rare variant carcinoma that displays histologic features of both ductal and lobular carcinomas, first reported by Fisher et al29 and about which only three case reports were published before the present case 11,22,26. A recent study also demonstrated that metastases of tubulolobular carcinoma could predominantly show tubules 30.…”
Section: Discussionmentioning
confidence: 59%
“…Although histopathological observation is often used to distinguish ductal from lobular carcinomas, the first and second results were contradictory. The patient may encounter tubulolobular carcinoma, a rare variant carcinoma that displays histologic features of both ductal and lobular carcinomas, first reported by Fisher et al29 and about which only three case reports were published before the present case 11,22,26. A recent study also demonstrated that metastases of tubulolobular carcinoma could predominantly show tubules 30.…”
Section: Discussionmentioning
confidence: 59%
“…Different from bone marrow metastasis and pericardial metastasis, 22 , 23 when the rare metastatic sites involve the skin or solid/hollow organs (especially an isolated uncommon metastatic site), local radiotherapy or complete resection can be performed for local intensive treatment on the basis of systemic therapy. 24 27 Different treatment patterns may lead to different prognoses for these patients with metastatic breast cancer. For selected patients with solitary adrenal metastases, laparoscopic adrenalectomy can provide a survival benefit.…”
Section: Discussionmentioning
confidence: 99%